Eczema herpeticum: a case report - M. S. KHAN, L. SHAW, V. CLARK, & Z. AFZAL (Paediatric Dentistry, 2005)
Eczema is not a condition commonly associated with primary herpetic gingivostomatitis. In some cases, however, a primary herpetic infection in a patient with eczema may result in a distinct acute dermatological condition known as eczema herpeticum.